CERTAIN PECULIARITIES IN THE STRUCTURE OF THE SUTURE LINE OF HETEROMORPH AMMONITES - Sharikadze M.Z.; Kakabadze M.V.; Kvantaliani I.V. (My University, 1989)
Interest in heteromorph ammonites has strongly increased in recent times due to the realization that these fossils are of great biostratigraphic and paleobiological importance. The earliest formed parts of their shell are rarely preserved as fossils, and each discovery of a whole specimen is thus a great event. That this is not an exaggeration is shown by the fact that of 100 apparently well preserved specimens of the late Barremian Matheronites Renngarten, 1926, only one was sufficiently complete for use in ontogenetic analysis. The history of study of this genus and questions of its systematic placement were discussed previously. In this paper, the authors present the results of morphogenetic analysis of Matheronites ridzewskyi Karak. Analysis of available material indicates that in heteromorph ammonites (principally members of the Families Ancyloceratidae and Heteroceratidae) the mode of development of suture lobes I and D has little or no systematic significance.